Multiple Sclerosis, Relapses, and the Mechanism of Action of Adrenocorticotropic Hormone - Perrin Ross, Amy; Ben-Zacharia, Aliza; Harris, Colleen J.; Smrtka, Jennifer (Frontiers in Neurology, 2013)
Relapses in multiple sclerosis (MS) are disruptive and frequently disabling for patients, and their treatment is often a challenge to clinicians. Despite progress in the understanding of the pathophysiology of MS and development of new treatments for long-term management of MS, options for treating relapses have not changed substantially over the past few decades. Corticosteroids, a component of the HPA axis that modulate immune responses and reduce inflammation, are currently the mainstay of relapse treatment. Adrenocorticotropic hormone (ACTH) gel is another treatment option. Although it has long been assumed that the efficacy of ACTH in treating relapses depends on the peptide’s ability to increase endogenous corticosteroid production, evidence from research on the melanocortin system suggests that steroidogenesis may only partly account for ACTH influences. Indeed, the melanocortin peptides (ACTH and α-, β-, γ-melanocyte-stimulating hormones [MSH]) and their receptors (MCRs) exert multiple actions, including modulation of inflammatory and immune mediator production. Melanocortin receptors are widely distributed within the central nervous system and in peripheral tissues including immune cells (eg, macrophages). This suggests that the mechanism of action of ACTH includes not only steroid-mediated indirect effects, but also direct anti-inflammatory and immune-modulating actions via the melanocortin system. An increased understanding of the role of the melanocortin system, particularly ACTH, in the immune and inflammatory processes underlying relapses may help to improve relapse management.